Numerical Study of the Effect of Blockage Ratio on the Flow Past One and Two Cylinders in Tandem for Different Power-Law Fluids - Cruchaga-Ssa., M; Castillo-Del Barrio, E; Aguirre-Ruz, A; Ruz-Nunez, O (Elsevier Inc., 2021)
In this work, the rheological behavior of power-law fluids on the flow dynamics is studied numerically. Studied cases include confined and non-confined problems that involve a single and two cylinders in tandem for 2-D and 3-D. For 2-D cases, the critical Reynolds numbers that define the Hopf bifurcation and its relation between the blockage ratio and the nature of the fluid are analyzed, including a complete CFD analysis. Results show that the blockage ratio, the addition of a second cylinder, and the rheological properties directly influence the flow s behavior. In this respect, the critical Reynolds number decreases by decreasing the power-law index and increasing the blockage ratio using shear-thinning fluids, and by increasing the power-law index in unconfined cases of shear-thickening fluids. For the 3-D case, different fluids are compared for a fixed Reynolds number and blockage ratio, proving that pseudoplastic fluids increase mixing capacity. © 2020 Elsevier Inc.